Application of ACO in Model Based Software Testing: A Review - Kaur, Navneet; Kaur, Jaskaranjit; Budwal, JS (International Journal of Computer Sciences and Engineering, 2025)
Software Testing is the process of testing the software in order to ensure that it is free of errors and produces the desired outputs in any given situation. Properly generated test suites may not only locate the defects in software systems, but also help in reducing the high cost associated with software testing. Model based software testing is an approach in which software is viewed as a set of states. There are a number of models of software in use today, a few of which make good models for testing. This paper introduces model-based testing and discusses its tasks in general terms with finite state models. Ant colony optimization (ACO) is best suited to model based software testing like finite state machines, state charts, the unified modeling language (UML) and Markov chains.